2016
DOI: 10.1177/0163278716684166
|View full text |Cite
|
Sign up to set email alerts
|

The Clinimetric Properties of Instruments Measuring Home Hazards for Older People at Risk of Falling: A Systematic Review

Abstract: Home hazards are associated with falls among older people living in the community. However, evaluating home hazards is a complex process as environmental factors vary according to geography, culture, and architectural design. As a result, many health practitioners commonly use nonstandardized assessment methods that may lead to inaccurate findings. Thus, the aim of this systematic review was to identify standardized instruments for evaluating home hazards related to falls and evaluate the clinimetric propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 108 publications
(87 reference statements)
2
44
0
6
Order By: Relevance
“…It is possible that a rater from a nonhealth background may not be able to accurately score the HOME FAST. The HOME FAST has demonstrated psychometric properties and it has a smaller number of items; therefore, it may be easy to use in terms of training and requires less time to complete, which may be preferable for clinicians . In addition, a pilot study conducted with the research assistants of the Malaysian Elders Longitudinal Research (MELoR) project indicated the HOME FAST was feasible to be used as clinical and research tool in the Malaysian context …”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible that a rater from a nonhealth background may not be able to accurately score the HOME FAST. The HOME FAST has demonstrated psychometric properties and it has a smaller number of items; therefore, it may be easy to use in terms of training and requires less time to complete, which may be preferable for clinicians . In addition, a pilot study conducted with the research assistants of the Malaysian Elders Longitudinal Research (MELoR) project indicated the HOME FAST was feasible to be used as clinical and research tool in the Malaysian context …”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Terwee et al indicated that one of the important aspects in establishing psychometric properties of an assessment tool is the ability of the tool to be generalised for practice and in cross‐cultural practice. However, many home hazard assessment tools lack generalisability to other cultural contexts and lack the capacity for the tools to be used by people from a variety of backgrounds …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To be effective as a screening tool, the HOME FAST‐HP needs to be able to identify older people with a currently unrecognized or unaddressed home hazard who may be at increased risk of a fall (Büttner & Muller, ). The HOME FAST‐HP has undergone extensive psychometric investigation since it was published (Rigby, Craciunoiu, Steir & Letts, ; Romli, Mackenzie, Lovarini, Tan & Clemson, ), including demonstrating predictive validity in relation to falls in a prospective study (Mackenzie, Byles & D'Este, ).…”
Section: Introductionmentioning
confidence: 99%